(untitled) (Physical Education, Health and Social Sciences, 2026)
Climate change–driven heatwaves are an increasing public health concern, yet their mental health impacts remain underexplored in rural populations of low- and middle-income countries. This quantitative cross-sectional study examined the association between heatwave exposure and mental health outcomes among young adults aged 18–35 years living in rural areas of Lahore, Pakistan. A total of 334 participants were selected using simple random sampling. Data were collected using standardized and validated instruments, including the Patient Health Questionnaire-9 (PHQ-9) for depression, Generalized Anxiety Disorder-7 (GAD-7) for anxiety, the Perceived Stress Scale, and the Pittsburgh Sleep Quality Index (PSQI). Heatwave exposure was operationally defined as repeated exposure to temperatures exceeding 40°C, along with assessment of access to cooling resources. Descriptive statistics indicated mild-to-moderate depressive symptoms, moderate anxiety levels, high perceived stress, and poor sleep quality among participants. Pearson correlation analysis revealed significant positive associations between heatwave duration and depression, anxiety, stress, and sleep disturbance (p < .001). Multiple linear regression analyses identified heatwave duration as a significant predictor of psychological distress, while coping capacity, employment status, and access to cooling facilities emerged as protective factors. Female participants reported significantly higher levels of stress and anxiety. The findings demonstrate that prolonged heatwave exposure is strongly associated with adverse mental health outcomes among rural young adults. These results highlight the need to integrate mental health screening and psychosocial considerations into heatwave preparedness and climate adaptation strategies, particularly in socioeconomically vulnerable rural communities.